2022
DOI: 10.1039/d1fd00101a
|View full text |Cite
|
Sign up to set email alerts
|

Studying the impact of the pre-exponential factor on templated nucleation

Abstract: Traditionally, the enhancement of nucleation rates in the presence of heterogeneous surfaces in crystallisation processes has been attributed to modification of the interfacial energy of the system according to the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 68 publications
3
4
0
Order By: Relevance
“…1, which was previously reported by Mealey et al. and used in previous work on glycine and diglycine crystallization 25, 29. true Jnormalhet normalor Jnormalhom = 1 tnormalind V …”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…1, which was previously reported by Mealey et al. and used in previous work on glycine and diglycine crystallization 25, 29. true Jnormalhet normalor Jnormalhom = 1 tnormalind V …”
Section: Resultssupporting
confidence: 66%
“…This paper continues previous research performed by the authors [25], which extended the concept of hydrogen bond complementarity to the crystallization of the simplest amino acid and dipeptide, glycine and diglycine, respectively. The findings were in line with other results centered around hydrogen bond complementarity, and it was found that diglycine was affected to a larger extent by the presence of the heteronucleant, namely, glass beads.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…This was potentially due to the enhanced number of probable non-covalent interactions between the hydrogen bond donor of glycine and its homopeptides and the hydrogen bond acceptor of the glass beads. This was further corroborated with the molecular dynamics simulations, which confirmed the enhanced residence time of triglycine on the surface of the glass beads due to an increased number of hydrogen bond interactions [13,14].…”
Section: Introductionsupporting
confidence: 71%